Multi-path direct current spinal stimulation extended survival in the SOD1-G93A model of amyotrophic lateral sclerosis - Ahmed, Zaghloul; Samaddar, Sreyashi; Hassieb, May; Sadek, Rodina; Morozova, Viktoriya; Begum, Sultana (Frontiers in Neurology, 2025)
IntroductionAmyotrophic lateral sclerosis (ALS) is a progressive neurodegenerative disease that affects motor neurons in the spinal cord and brain. We have developed a novel non-invasive approach, MultiPath-DCS, which utilizes direct current stimulation at multiple sites along the neural axis to provide simultaneous spinal and peripheral stimulation targeted at the affected limbs. MultiPath-DCS modulates the excitability of spinal cord neurons. This effect is significant for ALS, as motor neuron hyperexcitability is a fundamental characteristic of the disease.MethodsThis study used a transgenic mouse model of ALS (SOD1-G93A). Anodal-MultiPath-DCS was applied with six electrodes: three on the spine (centered on T13 and with an anodal polarity), two on the sciatic nerves (one on each nerve), and one on the abdomen. Mice were divided into two groups (stimulated vs. unstimulated or sham-stimulated). The stimulated animals received stimulation for one hour a day, three times a week, for three weeks. Survival was calculated from the onset of the disease and birth until the animal’s endpoint. We also performed various electrophysiological and molecular experiments to uncover the mechanism of action.ResultsWe demonstrated molecular changes induced by anodal MultiPath-DCS, including (a) reduced expression of mutant SOD1 protein, (b) decreased expression of elevated NKCC1, (c) reduced phosphorylated tau, (d) increased expression of HSP70, and (e) increased expression of LC3B. Additionally, we found that treatment with Anodal-MultiPath-DCS (anode on the spinal column) reduces long-term neuronal spinal excitability, slows the progression of muscle weakness, and extends the lifespan of stimulated mice. The mean survival time in the control group was 12.4 days. In comparison, the mean survival time in the stimulated group was 21.6 days using a therapeutic stimulation paradigm, representing a 74% increase in survival from disease onset. Spinal motor neuron survival showed a 54% increase in stimulated compared to non-stimulated groups.DiscussionCombined, this data provides evidence that Anodal-MultiPath-DCS reduces hyperexcitability and enhances the clearance of misfolded proteins by modulating autophagy and proteolytic systems. By decreasing spinal excitability and clearing toxic proteins from motor neurons, Anodal-MultiPath-DCS promotes survival and could serve as a disease-modifying intervention for ALS.